Language Function Analysis in Dadung by Geoffrey Leech - Putri Ayu Lestari; Ahmad Zaed Abdul Aziz (English Literature Department, Adab and Humanities Faculty, 2024)
Dadung is a musical art that describes the social culture of the people of the Jembatan Mas Village, Pemayung, Batanghari Regency, Jambi Province. This can be seen from the frequency with which the local community performs this art in the context of various cultural events, one of which is a wedding ceremony. The purpose of this study is to describe the language function of Dadung as one of oral tradition in Jambi. The analysis method utilises the theory of Leech (20023) meaning (Leech, 2003) thet tells about the language functions include informational, expressive, directive, aesthetic, and phatic. The results of this study indicate that every verse of Dadung has language function which the dominant is aesthetic functon. Dadung's origins came from ordinary people who fell in love with the king's daughter and wanted to make the king's daughter a companion for life, but because Dadung came from ordinary people, the princess refused Dadung's wishes. Disappointed, dadung recited poems that touched and melted her heart, then the daughter accepted dadung's proposal. In short, dadung eventually developed into an art popular with the people of Batanghari. Dadung is usually played on the wedding night as entertainment for the girl who is measuring coconuts. and mothers who are ready to cook.